Asuhan Kebidanan Intra Natal Care dengan Kasus Inersia Uteri di Rumah Sakit Umum Dewi Sartika Kota Kendari Tahun 2022 - Suhartati; Esse Tendry Nelly; Arbiyah (Jurnal Penelitian Sains dan Kesehatan Avicenna, 2022)
Background: Uterus inertia is a his with intensity that is less frequent than normal his. Uterus inertia is not a direct cause of maternal death but can be fatal if not handled properly. In 2019, there were 352 deliveries at Dewi Sartika Hospital, Kendari City, 21 of which were accompanied by uterine inertia. Objective: This study aims to study the pattern of midwifery care for mothers with uterus inertia. Methods: Observation of midwifery care management interviews 7 steps verney and SOAP (subjective, objective, assessment, plan). The subject of care is Mrs "S", selected by accidental sampling. The research was carried out from 9 July 2021 to 28 June 2022. Results: Mother's general condition was good, awareness was composmentis, TTV was within normal limits. Diagnosis of the actual problem G1P0A0 gestational age 39 weeks 1 day, intra-uterus, live fetus, single, left back, cephalic presentation, divergent, good condition of mother and fetus, preterm 1st stage of active phase with uterine inertia with potential data on prolonged labor, dehydration, fatigue, intrapartum infection and fetal distress. SpOG doctor collaboration, plan of care, namely checking every 4 hours or if there is an indication, monitor DJJ, His, contractions every 30 minutes, temperature and blood pressure every 4 hours. Conclusion: There is no gap between theory and field practice. The care provided is in accordance with Varney's 7-step midwifery care management.